Key Transformation Variables for the Lean Higher Education Success - Yassin, Yasni Nurul Huda Mohd; Bungsu, Mohd Sharial; Thangal, Thahira Bibi TKM; Nordin, Mohd Norazmi; Ismail, Azianti; Othman, Akmal Aini (CENTRAL ASIA AND THE CAUCASUS, 2022)
The higher education sector faced increasingly tense to transform due to the digitization that reshapes the world in the 21st century to strengthen and improve the teaching and learning environment. The present critical success factors driven from global-profit-making reform institutions are affected by both external and internal issues. This systematic article review expounds on the instrumental transformation variables that influence higher education institutions globally. The exploration of these variables is not a new phenomenon in this research field and has long gained the attention of numerous scholars. However, most of these past inquiries overlooked the effects of cultural and contextual components, where the perspectives of the higher education landscape is often underrepresented. Hence, this study aims to fill this gap by critically reviewing a considerable amount of past studies on the changes in Asian educational institutions. The Systematic Review approach was adopted for data analysis, accessing main journal databases and search engines through Elsevier, ResearchGate, Google Scholar, ScienceDirect, Web of Science, Scopus, Emerald and EBSCO. The search efforts resulted in a corpus of 50 articles were reviewed. As a result of the thematic analyses, thirteen main themes were formulated namely, Globalization, Income Generation and Financial Implication, Institutional Policies, Knowledge Management and, Learning Innovation, Governance in Institutional Restructuring, Synergy, Leadership, Research, ICT, Decision Making, Communication, Culture and Autonomy as variables for the higher education sector. Several recommendations were also presented for the reference of relevant parties and future scholars.